Peran Distribusi Pendapatan Pada Sektor Pertanian Di Desa Sambirampak Kidul - Eka Dwi Lestari; Fitria Romadhani; Nursiyati . (CV.ITTC INDONESIA, 2026)
The agricultural sector remains the backbone of the rural economy in Indonesia, including in Sambirampak Kidul Village. The distribution of income generated from the agricultural sector plays a crucial role in determining the level of welfare, economic equality, and social stability of rural communities. This study aims to analyze the role of income distribution in the agricultural sector and its impact on the socioeconomic conditions of the people of Sambirampak Kidul Village. This study used a qualitative method with a descriptive approach. Data were obtained through in-depth interviews with landowners, farm laborers, village officials, and community leaders, supported by field observations and documentation. The results indicate that the agricultural sector contributes significantly to village income, but income distribution remains unequal due to differences in land ownership, profit-sharing systems, and access to capital and agricultural technology. This inequality impacts the level of welfare between households. Therefore, farmer empowerment policies and programs are needed to encourage a more equitable and sustainable income distribution.